2013
DOI: 10.1075/intp.15.1.02che
|View full text |Cite
|
Sign up to set email alerts
|

Non-native accents and simultaneous interpreting quality perceptions

Abstract: A controlled experiment measured native Hong Kong Cantonese speakers' perceptions of the quality of three different simultaneous interpretations (SIs) into Cantonese. The SIs differed only in the interpreters' accents, native in one case and non-native in the other two. Participants were randomly assigned to one of three groups, listening to the following versions of the SI: (1) native-accented Cantonese (control group); (2) Mandarin-accented Cantonese; (3) Englishaccented Cantonese. To motivate participants t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…Therefore, at least from a practical perspective, the interpreter's non-native accent may not be a major issue as long as it does not attract listeners' attention to language flaws rather than to the message being conveyed (Donovan 2004). However, Cheung (2003Cheung ( , 2013 showed that conference participants listening to an interpreter with a non-native accent were more critical than those listening to an equivalent interpretation delivered in a native accent, though content was identical in the two cases. In the broader setting of language acquisition and use, Derwing and Munro (2009) argued that criticism can be conveniently directed at accent as a pretext for discriminating against the group of speakers thus identified.…”
Section: Perception Of Non-native Accentsmentioning
confidence: 59%
See 2 more Smart Citations
“…Therefore, at least from a practical perspective, the interpreter's non-native accent may not be a major issue as long as it does not attract listeners' attention to language flaws rather than to the message being conveyed (Donovan 2004). However, Cheung (2003Cheung ( , 2013 showed that conference participants listening to an interpreter with a non-native accent were more critical than those listening to an equivalent interpretation delivered in a native accent, though content was identical in the two cases. In the broader setting of language acquisition and use, Derwing and Munro (2009) argued that criticism can be conveniently directed at accent as a pretext for discriminating against the group of speakers thus identified.…”
Section: Perception Of Non-native Accentsmentioning
confidence: 59%
“…Unless very obvious mistakes are made, monolingual SI listeners often cannot assess accuracy and therefore tend to focus above all on the fluency of delivery when judging SI quality. Empirical studies have shown that fluency in general (Rennert 2010), and particular components of fluency such as prosody (Garzone 2003), intonation (Collados Aís 1998Aís /2002Holub 2010), pauses (Pradas Macías 2006) and native accents (Cheung 2003(Cheung , 2013, can influence how users perceive SI quality. However, the only evidence of interpreters being scapegoated as a corollary of this tendency is limited to the survey findings mentioned above; there seems to be a lack of observational and experimental data on the subject.…”
Section: Scapegoating Interpretersmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies, however, have been carried out on the effect of interpreters' foreign accents on the users' perception (e.g., Hale, Bond & Sutton 2011;Cheung 2013), and other studies indicate that non-native accents can adversely affect listener comprehension (Derwing & Munro 2009). Also, in the workload study commissioned by the AIIC in 2001, difficult accents were one of the main stressors mentioned.…”
Section: Accentsmentioning
confidence: 99%
“…Experimental research is scarce either because professionals are reluctant to be analysed by an external observer, or because many meetings are strictly confidential. Looking back on the specialised scientific journals published in the last few years we can see that, indeed, there is a great amount of works on CI that still focus on features of the interpreting process, such as cognitive considerations -memory (Timarova et al, 2014) or how to measure cognitive load in the simultaneous modality (Seeber, 2013;Seeber 2011); linguistic features -language in consecutive interpreting notes (Abuín González, 2012), English as the lingua franca (Albl-Mikasa, 2013); phonetics -non-native accents in the perception of quality in simultaneous interpreting (Cheung, 2013), or the similarities between closely-related languages such as Bosnian, Croatian and Serbian (Hlavac, 2013); situation characteristics -interpreting questions and answers sessions in international conferences (Chang & Wu, 2009); emotional considerations -interpreters' self-defence mechanisms (Monacelli, 2009) and interpreting under extreme circumstances (Meuleman & Van Besien, 2009). …”
Section: Research In Interpreting: First Steps and General Trendsmentioning
confidence: 99%